2017
DOI: 10.1111/ans.14062
|View full text |Cite
|
Sign up to set email alerts
|

Does the ileal brake mechanism contribute to sustained weight loss after bariatric surgery?

Abstract: Bariatric surgery is currently the most effective strategy for treating morbid obesity. Weight regain following significant weight loss, however, remains a problem, with the outcome proportional to the period of follow-up. This review revisits a well-established physiological neurohormonally-mediated feedback loop, the so called ileal brake mechanism, with a special emphasis on the gut hormone peptide tyrosine tyrosine. The manuscript not only highlights the potential role of the ileal brake mechanism in weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 68 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…In this study, we compared postoperative exercise by 4 weeks and regular management in the postoperative control group, and both groups were effective in reducing the improvement of weight, BMI, NC, WC, and HC indicators. One study on postoperative weight change found that the initial phase of rapid weight loss usually enters in the rst 3 months after bariatric surgery, followed by a slow phase and nally weight stabilization occurs, while the initial rapid weight loss is mainly due to a decrease in energy intake [13] .One of the reasons for the signi cant weight loss in both groups in this study may be due to the postoperative energy intake problem, which resulted in signi cant weight loss in both groups due to the intake being less than their own consumption. There was no statistical difference between the preand post-group changes in weight, BMI, NC, and WC in the two groups (P > 0.05), indicating that there was no statistical difference in the effect of the postoperative exercise intervention at 4 weeks versus the conventional postoperative management in the control group in reducing these indicators.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we compared postoperative exercise by 4 weeks and regular management in the postoperative control group, and both groups were effective in reducing the improvement of weight, BMI, NC, WC, and HC indicators. One study on postoperative weight change found that the initial phase of rapid weight loss usually enters in the rst 3 months after bariatric surgery, followed by a slow phase and nally weight stabilization occurs, while the initial rapid weight loss is mainly due to a decrease in energy intake [13] .One of the reasons for the signi cant weight loss in both groups in this study may be due to the postoperative energy intake problem, which resulted in signi cant weight loss in both groups due to the intake being less than their own consumption. There was no statistical difference between the preand post-group changes in weight, BMI, NC, and WC in the two groups (P > 0.05), indicating that there was no statistical difference in the effect of the postoperative exercise intervention at 4 weeks versus the conventional postoperative management in the control group in reducing these indicators.…”
Section: Discussionmentioning
confidence: 99%
“…Further, given the public health problem of obesity in Australia 64 and its association with the development of pancreatic cancer, 28,65 there is a need to determine the extent of contribution of obesity to the incidence of pancreatic cancer in Australia. Wilson et al 66 have recently published a study in which they have shown that using theoretical models aimed at targeting weight reduction, they could postulate a decrease in the incidence of pancreatic cancer over 25 years by 2.8-11.4% in men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Further, given the public health problem of obesity in Australia 64 and its association with the development of pancreatic cancer, 28,65 there is a need to determine the extent of contribution of obesity to the incidence of pancreatic cancer in Australia. Wilson et al 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of undigested food in the distal small intestine may trigger a higher secretion of ileal brake hormones (i.e. PYY, CCK and GLP-1) that inhibit secretion and motility to maximize absorption (14,81). Recently, a lower secretion rate of trypsin, amylase and lipase was observed in common channel aspirates after infusion of a liquid meal in patients after RYGB compared to controls (82).…”
Section: Effect On Pancreatic and Gallbladder Secretionsmentioning
confidence: 99%